Eleven years of cyberattacks on Chinese supply chains in an era of cyber warfare, a review and future research agenda (2021)
Purpose – The contribution of this study aims to twofold: First, it provides an overview of the current state of research on cyberattacks on Chinese supply chains (SCs). Second, it offers a look at the Chinese Government’s approach to fighting cyberattacks on Chinese SCs and its calls for global governance. Design/methodology/approach – A comprehensive literature review was conducted on Clarivate Analytics’ Web of Science, in Social Sciences Citation Index journals, Scopus and Google Scholar, published between 2010–2021. A systematic review of practitioner literature was also conducted. Findings – Chinese SCs have become a matter of national security, especially in the era of cyber warfare. The risks to SC have been outlined. Cybersecurity regulations are increasing as China aims to build a robust environment for cyberspace development. Using the Technology-organizationenvironment (TOE) framework, the results show that the top five factors influencing the adoption process in firms are as follows: relative advantage and technological readiness (Technology context); top management support and firm size (Organization context) and government policy and regulations (Environment context). Research limitations/implications – This review focuses on cyberattacks on Chinese SCs and great care was taken when selecting search terms. However, the author acknowledges that the choice of databases/terms may have excluded a few articles on cyberattacks from this review. Practical implications – This review provides managerial insights for SC practitioners into how cyberattacks have the potential to disrupt the global SC network. Originality/value – Past researchers proposed a taxonomic approach to evaluate progress with SC integration into Industry 4.0; in contrast, this study is one of the first steps toward an enhanced understanding of cyberattacks on Chinese SCs and their contribution to the global SC network using the TOE framework